2018
DOI: 10.1101/406827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional implications of impaired dynamic cerebral autoregulation in young healthy women; a comparative investigation

Abstract: Women exhibit higher prevalence of orthostatic hypotension with presyncopal symptoms compared to men. These symptoms could be influenced by an attenuated ability of the cerebrovasculature to respond to rapid changes in blood pressure (BP) [dynamic cerebral autoregulation (dCA)]. However, the influence of sex on dCA remains equivocal. We compared dCA in 11 women (25 ± 2 y) and 11 age-matched men (24 ± 1 y) using a multimodal approach including a sit-to-stand maneuver and forced oscillations (5 min of squat-stan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…We hypothesized that measuring AO precisely with a force sensor would identify previously unobserved variability in standing dynamics compared to estimating AO from a verbal command or other methods. (6,8,10,13) We have shown that while healthy young adults may demonstrate a faster transition reaction speed during a sit-to-stand dCA recording,(4, 8) older adults and individuals post-stroke may differ in their AO response. We have shown that the TD before the onset of dCA, which typically occurs within 10 seconds, (6,8,10,14) could potentially be skewed in some individuals by more than 2.5 seconds, which would directly affect dCA metrics.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We hypothesized that measuring AO precisely with a force sensor would identify previously unobserved variability in standing dynamics compared to estimating AO from a verbal command or other methods. (6,8,10,13) We have shown that while healthy young adults may demonstrate a faster transition reaction speed during a sit-to-stand dCA recording,(4, 8) older adults and individuals post-stroke may differ in their AO response. We have shown that the TD before the onset of dCA, which typically occurs within 10 seconds, (6,8,10,14) could potentially be skewed in some individuals by more than 2.5 seconds, which would directly affect dCA metrics.…”
Section: Discussionmentioning
confidence: 95%
“…Based on previously published methodology, the TD before the onset of the dCA regulatory response was measured as seconds between performing the sit-to-stand and a continuous increase in CVC without transient reduction (CVC = MCAv/MAP). (6,10) Rather than estimating AO in the recording as 60 seconds, our force sensor marks the exact AO time. We calculated the difference in the TD response when using the force sensor compared to estimating AO at 60 seconds, or when the participant was asked to stand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations